Dynamic Cerebral Autoregulation after Cardiopulmonary Bypass - Christiansen, Claus Behrend; Berg, Ronan M. G.; Plovsing, Ronni; Ronit, Andreas; Holstein-Rathlou, Niels-Henrik; Yndgaard, Stig; Møller, Kirsten (The Thoracic and Cardiovascular Surgeon, 2016)
Background Cerebral hemodynamic disturbances in the peri- or postoperative period may contribute to postoperative cognitive dysfunction (POCD) in patients undergoing coronary artery bypass grafting (CABG) with cardiopulmonary bypass (CPB). We therefore examined dynamic cerebral autoregulation (dCA) post-CPB and changes in neurocognitive function in patients that had undergone CABG.Materials and Methods We assessed dCA by transfer function analysis of spontaneous oscillations between arterial blood pressure and middle cerebral artery blood flow velocity measured by transcranial Doppler ultrasound in eight patients 6 hours after the cessation of CPB; 10 healthy volunteers served as controls. Neurocognitive function was assessed by four specific tests 1 day prior to and 3 days after CPB.Results Even though patients exhibited systemic inflammation and anemic hypoxemia, dCA was similar to healthy volunteers (gain: 1.24 [0.94–1.49] vs. 1.22 [1.06–1.34] cm mm Hg−1 s−1, p = 0.97; phase: 0.33 [0.15–0.56] vs. 0.69 [0.50–0.77] rad, p = 0.09). Neurocognitive testing showed a perioperative decline in the Letter Digit Coding Score (p = 0.04), while weaker dCA was associated with a lower Stroop Color Word Test (rho =  − 0.90; p = 0.01).Discussion and Conclusion We found no changes in dCA 6 hours after CPB. However, based on the data at hand, it cannot be ruled out that changes in dCA predispose to POCD, which calls for larger studies that assess the potential impact of dCA in the early postoperative period on POCD.
Keywords: cerebral autoregulation; cardiopulmonary bypass; postoperative cognitive dysfunction